Isolation of caffeine from the seeds of Leucaena leucocephala (Lam.) De Wit. (Family Leguminosae) - Evangelista, Liza F.; Cruz, Ileana R.; Concepcion. Adoracion B.; Fernando, Elena S. (Manila College of Pharmacy, University of the Philippines, 1988)
Caffeine may be isolated from roasted ipil-ipil seeds (Leuucaena leucocephala (Lam.) De Wit) by refluxing with alcohol for 6 hours.
Thin layer chromatographic methods revaled the similarity of caffeine obtained from ipil-ipil seeds to that of the standard caffeine and thus it can be concluded that ipil-ipil seeds may be a cheaper source of caffeine that may be utilized in certain pharmaceutical preparations.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1988.
Keywords: Caffeine; Lead tree; Ipil-ipil.